Analysis of Feeding White Eggs, Cockfish, Binahong Leaves, Belt Leaf Soak, VCO, Pineapple Juice and Honey on Accelerate Healing of Perineum Wounds and Incidents Perineal Wound Infection - Ita Herawati; Neneng Hasanah; Ihat Sutihat; Elvrida Triana BR Purba; Nurhaeni; Ervina Nursaleha; Yeni Nuraeni (Postgraduate, University of Mataram, 2024)
Perineal wounds, if not properly treated, are at risk of infection, especially with poor hygiene, inappropriate care, or comorbidities like diabetes. Symptoms of infection include worsening pain, swelling, redness, and fluid or pus discharge, sometimes accompanied by fever or chills. This research aimed to examine the effects of natural remedies—white eggs, snakehead fish, binahong leaves, soaked betel leaves, VCO, pineapple juice, and honey—on accelerating perineal wound healing and reducing infection risk. Using a quasi-experimental quantitative approach with purposive sampling, the study found that these remedies significantly accelerated wound healing compared to a control group, as indicated by a p-value of 0.000 from Mann-Whitney tests. While some in the control group experienced infections, those treated with the natural remedies showed faster healing and fewer infections. The study suggests that using these natural treatments can effectively speed up perineal wound healing and reduce the risk of infection.